Integrated effects of manures and fertilizers on the yield and nutrient uptake by BRRI dhan49 (Journal of the Bangladesh Agricultural University, 2014)
A field experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University (BAU), Mymensingh during Aman season of 2011 to evaluate the effects of manures and fertilizers for maximizing the yield of BRRI dhan49. The experiment had six treatments, laid out in a randomized complete block design (RCBD) with four replications. The treatments were T0 = Control, T1 = STB-CF (HYG), T2 = CD + STB-CF (HYG), T3 = PM + STB-CF (HYG), T4= CoM + STB-CF (HYG) and T5 = Farmers practice (FP). Organic manures including cowdung, poultry manure and compost were applied to the experimental plots @ 5, 3 and 5 t ha-1, respectively. The recommended dozes of N, P, K and S supplied from urea, TSP, MoP and gypsum were 90, 15, 60 and 15 kg ha-1, respectively. Yield contributing characters like plant height, effective tillers hill-1, panicle length and grains panicle-1 of BRRI dhan49 were significantly influenced by the application of manures and fertilizers. The highest grain yield of 4.87 t ha-1 was observed in the treatment T3 [PM + STB-CF (HYG)] and the lowest value of 3.61 t ha-1 was found in T0 (control). The straw yield ranged from 4.10 to 5.51 t ha-1 in different treatments. The NPKS uptake by BRRI dhan49 was markedly influenced by manures and fertilizers. Based on overall results, the treatment T3 [PM + STB-CF (HYG)] was found to be the best combination of manures and fertilizers for obtaining the maximum yield and quality of rice. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21240 J. Bangladesh Agril. Univ. 12(1): 67-72, June 2014